Bernard Häring and the Second Vatican Council - Hill, Brennan R. (Horizons, 2006)
This article examines the life and work of Bernard Häring, C.SS.R., especially his valuable contributions to the Second Vatican Council and his dedication to the council's vision of renewal. It begins with an overview of Häring's preconciliar religious and theological formation in his family, seminary and university, during World War II, and during his teaching in Rome. The next section deals with Häring's work at the council, especially his efforts on the original Theological Commission to resist the rigidity of the first drafts, and his contributions to Lumen Gentium ("The Constitution on the Church"), Unitatis Redintegratio ("The Decree on Ecumenism"), Dignitatis Humana ("The Declaration on Religious Freedom"), Gaudium et Spes ("The Constitution on the Church and the Modern World"), and Optatam Totius ("Decree on Priestly Formation"). The final section considers Häring's mission to spread the council's message of renewal to the world, his conflicts with the forces attempting to repress the progressive agenda, and his courageous visioning of what a renewed church might look like in the future.